Lignocellulosic waste materials as potential sorbents for the removal of surfactant and nutrients from environmental aqueous solution. - Vicente, Juvinch Regatona
Water pollution resulting from anthropogenic activities is a prevalent problem in developing countries. The potential of two common lignocellulosic waste materials (banana peel and rice husks) was evaluated for its application as sorbents for the removal of surfactants and nutrients from environmental aqueous solutions. The individual and effects of salinity (3 and 33 ppt) and pH (6 and 9) on the removal of surfactant and nutrients, as well as the possible interaction between these parameters were studied through batch sorption experiments. Results showed both banana peel and rice husks sorbents have potential for the removal of surfactants from surface water. However, the potential application of the above sorbent materials in the removal of surfactants from effluent water could not be conclusively established from the results of the present study. Moreover, results indicate that lignocellulosic waste materials may not be suitable sorbents to remove nutrients (N and P) from the surface and effluent waters evaluated in this study. Salinity levels of the environmental aqueous solutions were observed to have significantly influenced the removal of surfactants from surface water. Higher salinity enhanced the removal of surfactants from aqueous solutions for both lignocellulosic sorbents. On the other hand, pH indicated minimal effect on the removal of surfactants by the sorbents. Moreover, the interaction of pH and salinity showed detraction of surfactant and phosphorus removal from the aqueous solutions, but resulted in enhancement of nitrogen removal. Lastly, matrix effects and other factors may have influenced the removal of surfactants from the environmental aqueous solutions. The results of the present study provided a basis for the potential development of alternative and cost-effective techniques using sorbent materials, in the removal of common urban water pollutants, including surfactants and nutrients. The sorbents materials investigated in the present study are considered waste agricultural by-products. Thus, the utilization of these materials could also contribute to solid waste reduction.